Analysis of Factors Affecting Job Satisfaction and Impact to Burnout on Hopsitalization Nurses in General Hospital - Rahmi, Trisha Alya; Meilani, Yohana Cahya Palupi (Jurnal Ilmiah Sumber Daya Manusia, 2023)
Burnout is a pathological syndrome in which a maladaptive emotion develops in response to prolonged work stress. One of the causes of burnout is low job satisfaction, so it can affect various aspects of work. Job related factors are usually considered acceptable for interventions or strategies to increase satisfaction. Factors from job related itself are working conditions, work autonomy, and work family conflict. Purpose: to determine the factors that influence job satisfaction on nurses at a government hospital in Pemalang Regency. Design: From the total of 160 respondents, there were 30 male respondents and 130 female respondents. The majority group of respondents was in the range of 31 - 40 years old. In terms of education, 48.8% with D3 Nursing education. 94.4% of respondents are married. On average, respondents have worked for > 5 years (85%) and 91.9% of respondents have working hours of 41 – 59 hours/week. The results show that job satisfaction is proven to have negative effects on burnout. Result: The result model (empirical model) of this study is known to have substantial small predictive accuracy (R2) and medium predictive relevance (Q2) on burnout as the predicted dependent variable. Conclusion: Therefore, it can be concluded that the antecedents of job satisfaction in this research model can adequately predict job satisfaction variables. Thus, this research model can be suggested to be replicated and tested further in other nurse populations at other hospitals that are potential for future research.